Kebutuhan Informasi Petani terhadap Informasi Standar Indikasi Geografis dan Pemasaran Kopi Arabika Java Sindoro-Sumbing - Retno Rahayu Slamet; Hanifah Ihsaniyati; Arip Wijianto (AGRITEXTS: Journal of Agricultural Extension, 2020)
This research aimed to analyse information needs for standard of geographic indication and marketing, analyse factors which affected information needs for farmers’ towards standard information of geographic indication and marketing of Arabika Java Sindoro-Sumbing coffee, and analyse correlation between the factors which affected information needs for farmers’ with standard of geographic indication and marketing of Arabika Java Sindoro-Sumbing coffee. Basic method of the research used was quantitative methods with survey technique. The research location was in Kledung Sub-district, Temanggung Regency with the consideration of this sub-district is secretariat of MPIG Arabika Java Sindoro-Sumbing coffee. The sampling used technique of purposive random sampling that consisted of sixty respondents. The data analysis used correlation test of Rank Spearman  with SPSS Statistics 17.0 program. The research result showed that: (1) Information needs for farmers’ towards standard of geographic indication and marketing of KAJSS included in the urgently needed category (2) Farmers’ age included in the high category, job included in the high category, residence included in the near category, the last education included in the low category, the ability of accessing information included in the high category (3) There was significant correlation between farmers’ job and residence with information needs for farmers’ towards standard of geographic indication and marketing information of Arabika Java Sindoro-Sumbing coffee, there was not significant correlation between age, the last education, and the ability of accessing information towards information needs for standard of geographic indication and marketing information of Arabika Java Sindoro- Sumbing coffee.